DESCRIPTION OF PERSONAL HYGIENE AND CONTAMINATION OF WORM EGG UNDER THE NAIL OF GARBAGE TRANSPORT OFFOCERS AT THE DEPARTMENT OF PUBLIC WORKS AND SPATIAL PLANNING, JAMBI CITY - Gustomo Yamistada; Jessy Novita Sari (Poltekkes Kemenkes Jambi, 2020)
Background: Helminthiasis is a factor that affects the quality of human resources by inhibiting physical growth, children's intelligence and work productivity. Until recently, worms remained a problem due to the social and economic conditions in some parts of the world. The purpose of this study was to describe the cleanliness of nails, the use of gloves, and the presence of worm eggs on the nails of the garbage transport officers at the Department of Public Works and Spatial Planning, Jambi City. Method: This is a descriptive survey research. The sample in this study was 15% of the population, namely 38 garbage collectors from the Public Works and Spatial Planning Office of Jambi City. Descriptive data analysis. Results: The nail cleaners of the garbage transport officers at the Public Works and Spatial Planning Office of Jambi City were included in the good category as many as 6 officers (16%) and the nail cleaners who were included in the bad category were 32 officers (84%). The use of gloves from the Public Works and Spatial Planning Office of Jambi City officials was 7 officers (18%) and 31 officers (82%) used gloves that were in the bad category. There were 25 samples (66%) of the garbage transporters from the Public Works and Spatial Planning Office of Jambi who were negatively contaminated with worm eggs and 13 samples (34%) who were positively contaminated with worm eggs. Conclusion: The cleanliness of nails and the use of gloves is not good and there is contamination of worm eggs from the garbage transporters of the Public Works and Spatial Planning Office of Jambi City